Effectivity of Inductive Method in Learning Nahwu-Sharaf at MIN 3 Banda Aceh City - Afriati, Intan; Siregar, Rahmat Sapaat; Fonna, Azhara; Muna, Zahratul (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to assess the effectiveness of the inductive method in improving the learning outcomes of Nahwu-Sharaf in MIN 3 Banda Aceh City. The use of inductive methods in Nahwu-Sharaf learning begins with the presentation of concrete examples that are analyzed by students to find common methods related to Nahwu-Sharaf material. This article is a qualitative research with a case study design. Data collection techniques include classroom observations, interviews, and documenting students' academic work. The results show that with the application of the inductive method, students are able to achieve an understanding at the conceptual level of the structure of the Arabic language both in terms of Sharaf and Nahwu. Students become more active, motivated, and demonstrate more advanced analytical thinking skills in drawing conclusions from given examples. These findings suggest that inductive methods offer significant potential for developing meaningful, student-centered learning.